Thin-film transistor arrays for biological sensing systems. (1st June 2022) - Wang, Dongping; Liu, Zhe; Li, Jun; Tang, Wei; Huang, Yukun; Yu, Jun; Xu, Longqian; Huang, Qi; Song, Yawen; Wang, Linzhi; Jin, Haihan; Xi, Kerui; et al.
Abstract: Thin-film transistor (TFT) active matrix (AM) arrays have been developed to achieve many applications, including flat panel displays, digital x-rays, digital microfluidics (DMF) and high-throughput biosensors. Here, we focus on a review on TFT array technologies for biological sensing systems, which are regarded as one of the most promising emerging application fields of TFTs. As an important part of the biological sensing system, the DMF chip will be introduced. In particular, development of the TFT-based AM DMF (AM-DMF) chips, which possess the characteristics of higher throughput and higher flexibility of manipulating liquid samples, will be discussed in details. Further, the developed TFT array based biological sensing systems will be summarized and discussed as well. Finally, we present prospects for AM-DMF chips and biosensors, along with a brief conclusion.